Attention to context during evaluative learning and context-dependent automatic evaluation: A cross-cultural analysis - YE, Yang (Institutional Knowledge at Singapore Management University, 2017)
Previous research has shown that changes in automatic evaluations can be limited to the context in which counterattitudinal information was acquired. This effect has been attributed to enhanced attention to context cues during the encoding of expectancy-violating counterattitudinal information. Drawing on previous evidence for cultural differences in attention to context and tolerance for inconsistency, the present research examined cultural differences in responses to conflicting evaluative information and the resulting context-effects on automatic evaluation. Study 1 revealed that both Canadian and Singaporean participants showed enhanced attention to context during exposure to counterattitudinal information. In a reanalysis of studies with Singaporean participants, Study 2 replicated the pattern of contextualized changes of automatic evaluations previously obtained in Western participants. The results suggest that contextualized change of automatic evaluations might be a general phenomenon that replicates across cultures. Implications for East-West similarities in basic attentional processes and automatic evaluation are discussed.